Ceremonia de Clausura - Chávez Peón, Federico; Blanca, Ramón; Kravzov, Jaime; Iglesias Garcia, Mario; Rodriguez Concha, Manuel; Pacheco Ceballos, Vicente (Revista Mexicana de Ingenieria Biomedica, 2018)
Invitados de Honor Actividades sociales